OCCURRENCE OF THE PUERULUS LARVAE OF THE INDIAN SPINY LOBSTER, PANUURUS HOMARVS (LINN.), IN COCHIN BACKWATER - Kathirvel, M (Indian Journal of Fisheries, 2011)
The occurrence of puerulus larvae of the Indian spiny lobster, Panulirushomarus (Linn.) in ttÂ» Cochin backwater is reported. Being the first record ofthese larvae frcmi Indian waters, brief notes on the puerulus, its metamorphosisto postpuerulus